2022
DOI: 10.1001/jamanetworkopen.2022.1754
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations and Mortality From Non–SARS-CoV-2 Causes Among Medicare Beneficiaries at US Hospitals During the SARS-CoV-2 Pandemic

Abstract: IMPORTANCEThe increased hospital mortality rates from non-SARS-CoV-2 causes during the SARS-CoV-2 pandemic are incompletely characterized. OBJECTIVE To describe changes in mortality rates after hospitalization for non-SARS-CoV-2 conditions during the COVID-19 pandemic and how mortality varies by characteristics of the admission and hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 37 publications
2
63
0
Order By: Relevance
“…Although some positive consequences have resulted from these challenges, including the move to routine virtual health care and the increased attention on staffing and supply chain sustainability, these positive consequences have been overwhelmed by the pandemic's negative impacts on health. Dang et al 1 Perhaps the most striking finding from the study 1 was that increased mortality was observed in hospitals with more COVID-19-related admissions, confirming the far-reaching consequences of COVID-19-related strain on the health care system. Strain, which is defined as nearing or exceeding the limits of the care team's ability to provide high-quality care to all patients who require it, 2 is a phenomenon that is intimately familiar to clinicians during COVID-19 but that can be challenging to quantify and study.…”
mentioning
confidence: 63%
“…Although some positive consequences have resulted from these challenges, including the move to routine virtual health care and the increased attention on staffing and supply chain sustainability, these positive consequences have been overwhelmed by the pandemic's negative impacts on health. Dang et al 1 Perhaps the most striking finding from the study 1 was that increased mortality was observed in hospitals with more COVID-19-related admissions, confirming the far-reaching consequences of COVID-19-related strain on the health care system. Strain, which is defined as nearing or exceeding the limits of the care team's ability to provide high-quality care to all patients who require it, 2 is a phenomenon that is intimately familiar to clinicians during COVID-19 but that can be challenging to quantify and study.…”
mentioning
confidence: 63%
“…Third, some unmeasured confounders could not be adjusted for in the analysis, such as behaviors that are associated with getting vaccinated and mortality. Fourth, there could be variation in outcome by medical center, as previous literature has demonstrated worse outcomes in areas with more cases of COVID‐19 [ 20 ]. However, matching by medical center was not feasible due to power.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Another contributor to excess mortality during the pandemic is an increase in deaths from non‐COVID‐19 causes, presumably from disruption of regular medical care and social services. 28 A recent survey found that forgone medical care was more common among those with mental health problems. 35 The social isolation caused by the pandemic might also more negatively affect the health of patients with psychiatric disorders and can contribute to excess deaths.…”
Section: Discussionmentioning
confidence: 99%
“…COVID‐19 infections were identified as the first Medicare claim (inpatient, SNF, outpatient, and carrier claims) with a diagnosis code of U07.1 in the10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD‐10‐CM) on or after April 1, 2020. 28 COVID‐19 fatality was defined as death within 30 days of first COVID‐19 diagnosis. A sensitivity analysis using death within 60 days was also conducted.…”
Section: Methodsmentioning
confidence: 99%